SEM study of the microelement composition of the apical region of the tooth after the treatment of destructive periodontitis - V. V. Glinkin; Z. S. Khabadze; Y. A. Generelova; M. A. Gasbanov; F. V. Badalov; O. Leizerovitz (Эндодонтия Today, 2023)
Relevance. Trace elements play an important role in the life of the cell. Using a scanning electron microscope (SEM), the microelement composition of dentin and cement of the apical region of teeth previously treated for destructive chronic periodontitis in the acute stage was studied.Aim. Using a scanning electron microscope to study the microelement composition of the apical area of hard tissues of the tooth root after the treatment of destructive periodontitis.Materials and methods. To determine the presence of certain trace elements in the composition of solid tissues, we used spectral analysis performed on a JSM-6490LV scanning electron microscope (JEOL, Japan) and an INCA Penta FETx3 energy-dispersive spectrometer (Oxford, England).Results. After endodontic treatment, the content and ratio of Ca and P in the hard tissues of the resorbed apex of the tooth root changes. The presence of newly formed highly mineralized cement was found. The ratio of microelements Ca/P and Na/Mg in the cement before and after the treatment of destructive periodontitis changes. Conclusions. An increased oxygen content may indicate the presence of active forms of this element in the cells. An increased content of Na in hard tissues testifies in favor of triggered regenerative processes. Perhaps the use of Cacontaining drugs helps cells form the structure of the tissue.Conclusions. After a certain period of time, after the treatment of destructive periodontitis, calcification of the hard tissues of the apical region of the tooth root occurs. The changing ratio of trace elements indicates the predominance of regenerative processes in the tissues of the tooth.